Examınıng The Perspectıve Of School Management Team On The Declıne In Learners Takıng Entrepreneurıal Subjects In Secondary Schools In Selected Dıstrıcts Of The Lımpopo Provınce - Khutso Pitso Mankgele (Cita Konsultindo Research Center, 2023)
In recent years, there has been a decline in the number of learners opting to take entrepreneurial subjects in secondary schools. significance of entrepreneurial subjects is empowering learners for the future in this ever-changing global economy. The purpose of the study is to examine the perception of the school management team on the decline in learners taking entrepreneurial subjects in selected districts of the Limpopo Province. The study used a qualitative research method, where eight school management team were interviewed,with majority